Rancang Sistem Deteksi Dini Terjadinya Kebakaran Menggunakan Logika Fuzzy pada Area Parkiran - Kresna Dana, I Gusti Putu; Suputra, Putu Hendra (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2025)
This research discusses the development of a fire monitoring system for semi-outdoor multi-story car parks using Internet of Things (IoT) technology. The experimental research method was used with the stages of the design science research method (DSRM). The system uses MQ-2, DHT11, and YG-1006 sensors to detect smoke, temperature rise, and flames. Data from the sensors is processed using fuzzy logic to determine the level of danger by the Arduino Uno microcontroller and notifications are forwarded through the LCD display to the security personnel. The test results show that the system is capable of producing digital values that represent the level of danger based on environmental conditions. The conclusion states that this system has the potential to improve responsiveness and reliability in the face of fire hazards in semi-outdoor multi-story car park environments.